Viktordningen: ett analytiskt perspektiv (Sociologisk Forskning, 2013)
The weight order – an analytical perspectiveThis article is an outline of a critically oriented and empirically grounded theory of the weight order, as a complement to theories of more widely recognized and studied ordering systems. We 1) expose the weight orders “absent presence” in humanistic and social science-oriented research treating overweight and fatness as a personal or social problem, 2) outline the contours and characteristics of this specific ordering system, and 3) suggest a set of sensitizing concepts for analysis of this ordering system. Two primary forms of activity, maintaining order and putting in order, are analysed. The first is making thin people into order and overweight people into disorder, and thus maintains order in the weight order. The other, putting in order, covers different activities supposed to make sure that people keep their bodies thin or try to become thin. These ordering activities meet resistance when overweight people stop dieting and/or define overweight as a personal choice and themselves as good enough, or even healthy and beautiful. We call these forms of resistance alternative weight-doings.
Keywords: the weight order; ordering; overweight; body weight; grounded theorizing